Perancangan Mesin Pencacah Plastik Tipe Shredder dan Alat Pemotong Tipe Reel - Naufal Yudha Triadi; Budhi Martana; Sigit Pradana (Jurnal Rekayasa Mesin, 2020)
Plastic is an object that can support human daily activities due to its character that is practical and resistant. However, wasted plastic can pollute the environment since it is difficult to be decomposed. The purpose of this study was to produce plastic chopper machine that is capable of chopping plastic waste with shredder type and reel type cutting tools. The design process is chosen based on a predetermined assessment. The kinds of plastic that are chopped will be PET (polyethylene terephthalate) and HDPE (high density polyethylene) plastic. AISI 304 material knife was chosen to chop up plastic waste. According to the results of design and calculation, the engine size has dimensions of 1105.6x1355.7x600, 3 HP motor drive power, and has a rotation of 1450 rpm which is assisted by pulley transmission elements and v-belt type A. The chopper components used consist of 14 pieces of shredder blade and 9 blade reel cutters with 2 pieces of bedknife. The components of shredder knives, reel knives, and frames are analyzed using Finite Element Analysis to determine the safety of the planned design.